Cordelia Heß. The Absent Jews: Kurt Forstreuter and the Historiography of Medieval Prussia - Maleszka, Mateusz (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2019)
Cordelia Heß. The Absent Jews: Kurt Forstreuter and the Historiography of Medieval Prussia. New York–Oxford: Berghahn Books, 2017. 334 pp + 1 map, 1 table. ISBN: 978-1-78533-492-4. [review]